Male pattern baldness and incidence of prostate cancer: A systematic review and meta-analysis. Issue 28 (July 2018) - He, Huadong; Xie, Bo; Xie, Liping
Abstract: Background: The relationship between male pattern baldness and incidence of prostate cancer remains inconclusive. Hence, we performed the present meta-analysis based on all eligible cohort and case–control studies. Methods: A comprehensive literature search was performed in October 2017 based on PubMed and Web of Science databases. Pooled relative risk (RR) and its 95% confidence interval (95% CI) was calculated with a DerSimonian and Laird random-effects model. Results: A total of 15 studies were included in this meta-analysis. Overall, no statistically significant association between baldness (any pattern) and prostate cancer risk was identified (RR: 1.03, 95% CI 0.96–1.11). There was obvious heterogeneity across included studies ( P < .078 for heterogeneity, I 2 = 36.4%). When subgroup analysis by types of baldness, a statistically significant association was observed for vertex baldness (RR 1.24, 95% CI 1.05–1.46) but not for other types of baldness. Conclusion: Individuals with vertex baldness may have an increased risk of prostate cancer. Given the obvious heterogeneity and null results in overall analysis and most of subgroup analyses, further large well-designed prospective cohort studies are warranted to confirm our preliminary findings.